Upcycling high-impact polystyrene waste into fiber membranes incorporated with titania for water filtration applications - Muhammad Fahroji; Ratih Amalia; Bagas Haqi Arrosyid; Putri Hawa Syaifie; Muhammad Miftah Jauhar; Afif Akmal Afkauni; Arramel; Didik Aryanto; Akmal Zulfi; Alfian Noviyanto (Cleaner Materials)
The extensive use of plastics has led to a significant increase in solid waste, necessitating innovative approaches for waste management and resource recovery. This study presents an upcycling pathway by synthesizing fiber membranes from high-impact polystyrene (HIPS) waste combined with TiO2 through electrospinning. To the best of our knowledge, this is the first study to fabricate HIPS-TiO2 membranes for water filtration and photocatalytic applications. The inclusion of TiO2 enhanced membrane morphology by increasing fiber diameter and optimizing porosity, with the 0.5 wt% TiO2 composition yielding bead-free fibers and the smallest porosity. While TiO2 did not alter the water contact angle (WCA), it significantly improved membrane performance. Pseudo-first order kinetic fits (k = 0.0027–0.0037  h−1, R2 up to 0.975) demonstrate rapid MB degradation, with 0.5 wt% TiO2 reaches complete removal within 1.5 h under ultraviolet light, outperforming other compositions. The membranes achieved a pure water flux (PWF) of 589.7 ± 1.22 Lm-2h−1 and demonstrated excellent rejection rates of over 95 % for antacid suspensions. These results highlight the potential of HIPS-TiO2 membranes as a sustainable alternative to conventional filtration materials, addressing both plastic waste and water purification challenges. Future research could explore the long-term stability and scalability of these membranes for industrial water treatment applications, further advancing their contribution to the circular economy.